155k views
3 votes
Given g(-2) = -4 and g'(-2) = 5, find the value of h'(-2) based on the function below.

h(x) = (-2x + 6) • g(x)

User Tuseau
by
5.8k points

1 Answer

3 votes

Explanation:

so,

h(x) = f(x) × g(x)

h'(x) = f'(x) × g(x) + f(x)×g'(x)

with f(x) = -2x + 6

f'(x) = -2

so,

h'(-2) = -2 × g(-2) + (-2×-2 + 6) × g'(x) =

= -2 × -4 + 2 × 5 = 8 + 10 = 18

User Pawan Verma
by
4.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.